Analisis Bentuk Islamophobia Global: Studi Komparasi Antara Indonesia, India dan Perancis - Willi Ashadi (Rayah Al-Islam, 2025)
This study seeks to examine the development of Islamophobia around the world following the September 11, 2001 terrorist attacks that destroyed the World Trade Center in the United States and killed 2,977 people. The 9/11 incident triggered a "war on terror" campaign by U.S. President George W. Bush that focused on Islam and extremist groups such as Al-Qaeda. In addition to China and Russia, the United States—as a superpower—perceived Islam as a significant potential threat to global stability, given Islam’s historical role as a major power. This campaign indirectly fueled hatred toward Islam, known as Islamophobia, which influenced many countries in the West, Europe, and Asia. This study aims to analyze the various forms of Islamophobia in India, France, and Indonesia between 2013 and 2024, using a qualitative method and primary data sources such as books, journals, media, and research reports.